Towards new milestones in our quest to go beyond the standard model : proceedings of the International School of Subnuclear Physics - Zichichi, Antonino (Subnuclear series, 2007)
This volume is a collection of lectures given by distinguished physicists from around the world, covering the most recent advances in theoretical physics and the latest results from current experimental facilities. Following one of the principal aims of the School - to encourage and promote young physicists to achieve recognition at an international level - the students who distinguished themselves for the excellence of their research were given the opportunity to publish their presentations in this volume. Sample Chapter(s). Chapter 1: Experimental Signatures of Strings and Branes (2,702 KB).